No entry without strategy : building the rule of law under UN transitional administration - Bull, Carolyn Gardner, 1969- (United Nations University Press, 2008)
For international actors seeking to consolidate peace and democracy in disrupted states, the importance of establishing the rule of law is now well-recognized. UN peace operations have struggled to ensure lasting security against violence and to build legitimate structures to redress disputes peacefully. UN actors have confronted a fundamental dilemma: if embedding the rule of law rests on complex political and social transformations regarding conflict, power and the state, can external actors make a difference? The book investigates the challenges faced by UN transitional administrations in establishing the rule of law in Cambodia, Kosovo and East Timor. In so doing, it explores conceptual understandings of the UN's state-building agenda and speaks to broader questions about the role of external actors in disrupted states.--Publisher's description.